2021
DOI: 10.1088/1741-4326/ac0bfb
|View full text |Cite
|
Sign up to set email alerts
|

Tearing mode stabilization by electron cyclotron resonant heating in EAST tokamak experiments

Abstract: Tearing mode stabilization by electron cyclotron waves (ECWs) has been carried out in Experimental advanced superconductiong tokamak (EAST) experiments. The effects of the amount of ECW power and the radial wave deposition location on stabilizing the m/n = 2/1 magnetic island are investigated, where m/n is the poloidal/toroidal mode number. The local heating is found to dominate the mode stabilization in these experiments. The stabilization is more effective when the wave is deposited closer to the radial isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…The effects of ECW power and the deposition position on the mode stabilization have been investigated. The NTM stabilization is found to be sensitive to the ECW deposition location, being different from the tearing mode stabilization by the electron cyclotron resonant heating (ECRH) in previous EAST experiments [24]. More interestingly, it is found that the NTM can be avoided when applying ECCD earlier during the ramp-up phase of the RMP amplitude, if the ECCD is always around the O-point of the magnetic island, indicating an efficient way for avoiding locked modes that can lead to the major disruption of tokamak plasmas.…”
Section: Introductioncontrasting
confidence: 82%
“…The effects of ECW power and the deposition position on the mode stabilization have been investigated. The NTM stabilization is found to be sensitive to the ECW deposition location, being different from the tearing mode stabilization by the electron cyclotron resonant heating (ECRH) in previous EAST experiments [24]. More interestingly, it is found that the NTM can be avoided when applying ECCD earlier during the ramp-up phase of the RMP amplitude, if the ECCD is always around the O-point of the magnetic island, indicating an efficient way for avoiding locked modes that can lead to the major disruption of tokamak plasmas.…”
Section: Introductioncontrasting
confidence: 82%
“…It is evident that a sufficient amplitude of Resonant Magnetic Perturbations (RMPs) can destabilize the tearing mode and induce a large magnetic island. The generated magnetic island is in phase with the RMP due to the applied electromagnetic torque and the width of the island is proportional to the RMP amplitude [25]. An analysis of the TOF signals due to the mode dynamics can be studied accurately in more detail when the applied RMP and the island rotate slowly.…”
Section: /1 Tearing Modementioning
confidence: 99%
“…For example, the radiative cooling from impurity SPI into the island could result in both current holes and pressure holes on the O-point, [16,40] while the electron cyclotron wave injection (like ECRH) could result in bumps within the island for both profiles. [3][4][5][6] More bizarre cases could exist, for example during hydrogen isotope injections, where the dilution cooling resulted in current expulsion from the island interior but didn't deplete the pressure due to the low radiation power. Indeed, there might even exist a minor pressure peak within the island due to the heat transfers into the low temperature, but high density, island region.…”
Section: Quasi-linear Perturbed Equilibrium and Profile Modification ...mentioning
confidence: 99%
“…[1] Such damage during the thermal quench (TQ) phase of disruptions is characterized by a large amount of thermal load on the plasma facing components (PFCs), [1] while the most feared disruptive consequence in the current quench (CQ) phase is the localized deposition of a large amount of runaway electrons. [2] To avoid such damages and safely guard the continued operation of future high performance devices, various disruption avoidance systems (DAS) are designed, such as the electron cyclotron current drive (ECCD) or Heating (ECRH), [3][4][5][6] to suppress the instability of the dominant magnetic islands by modifying the current and pressure profile within. Facing this, disruption mitigation systems (DMS) such as the shattered pellet injection (SPI) [7][8][9][10][11][12][13][14][15][16][17] or other massive material injection (MMI) [18][19][20][21][22][23][24][25] techniques are used to deplete the majority of thermal energy via radiation loss during the TQ, and raise the density to help with runaway electron suppression during the CQ phase.…”
Section: Introductionmentioning
confidence: 99%